The human talent competitions of auctioneers in the efficiency of auctions in Peru - Tello Pérez, José Carlos (2020)
The objective of this article is to determine the influence between the level of the human talent competences of the auctioneers and the efficiency in the auctions, both in the influx of bidders and in the level of prices awarded. Thus a good training of an auctioneer will assume the motivation to carry out the attraction of new bidders, in addition to the persuasive capacity to increase the bid price of the bidders for a greater expectation of importance of the auctioned good. As a result of this study, it is observed that there is a significant relationship, in terms of motivating attitude and persuasion, as notable talents in the efficiency of the bidder, which must be constantly evaluated by the institutional management of the National Program of Seized Assets (PRONABI).